Icosahedral Carbaboranes with Peripheral Hydrogen–Chalcogenide Groups: Structures from Gas Electron Diffraction and Chemical Shielding in Solution. Issue 9 (16th January 2019) - Baše, Tomáš; Holub, Josef; Fanfrlík, Jindřich; Hnyk, Drahomír; Lane, Paul D.; Wann, Derek A.; Vishnevskiy, Yury V.; Tikhonov, Denis; Reuter, Christian G.; Mitzel, Norbert W.
Abstract: Carbaboranes 1, 2‐(EH)2 ‐ closo ‐1, 2‐C2 B10 H10 (E=S, Se) were prepared, in the case of E=Se for the first time. Their semi‐experimental equilibrium molecular structures were established by the concerted use of quantum‐chemical calculations and gas electron diffraction. A method was developed and implemented to quantify the contribution of experimental data to each refined structural parameter. The accuracy of the experimental structures and those calculated at the MP2 level of theory were gauged by comparison of experimental 11 B NMR chemical shifts with quantum‐chemically computed values; the inclusion of electron correlation (GIAO‐MP2) provided superior results. For the purpose of geometrical prediction, the remaining group 16 elements were considered, and the icosahedral structures for E=O and Te were also computed; for E=O the same theoretical approach was used as for E=S, and for E=Te a description similar to that for E=Se was employed. Abstract : Hydrochalcogeno carbaboranes : Icosahedral carbaboranes with thiol and selenol groups were prepared and their structures determined by gas electron diffraction augmented by ab initio calculated data (see figure). A method for quantifying the experimental contribution to the structural parameters was developed and tested. Comparison of NMR chemical shifts in solution with quantum‐chemically calculated values allowed further structural information to be retrieved.